Nanoemulsion Purified Catechin Gambir (Uncaria gambir Roxb.): Formulation and Antimicrobial Activity against Staphylococcus aureus, Pseudomonas aeruginosa, and Enterobacter aerogenes - Muhtar, Nurul Inaya; Mita, Soraya Ratnawulan; Kusuma, Sri Agung Fitri (Sarana Ilmu Indonesia (Salnesia), 2025)
Gambir (Uncaria gambir Roxb), a plant native to Indonesia, has long been recognized in traditional medicine. The primary active component in gambir is catechin, which possesses various biological activities, including broad-spectrum antimicrobial properties. However, catechin faces challenges related to low stability, necessitating its formulation into a nanoemulsion to enhance both its stability and effectiveness. This study aims to evaluate whether an optimized nanoemulsion formulation of catechin can improve its antimicrobial activity. The methodology includes assessing the antimicrobial effectiveness of catechin powder and catechin nanoemulsion using the agar diffusion method, as well as determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) through the microdilution method. Antimicrobial activity was tested against three bacterial strains: Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 9027, and Enterobacter aerogenes ATCC 13048. The optimal formulation consisted of a combination of Tween 80 and Span 80 as surfactants (15%), PEG 400 as a co-surfactant (7%), and isopropyl myristate (IPM) as the oil phase (10%). This nanoemulsion formulation demonstrated a transmittance value of 91,9%. Based on the antimicrobial activity results, the catechin nanoemulsion exhibited enhanced antimicrobial effects compared to catechin powder. The nanoemulsion containing 2% catechin showed the highest antimicrobial activity against all three tested bacteria. These findings are expected to provide new insights into the potential application of catechin nanoemulsion as a more effective antimicrobial agent.